Phusis and Nomos in Plato - Zahra Nouri Sanghdehi (Journal of Philosophical Investigations, 2017)
One of the greatest problems in Plato that appears in different forms in his works is the relation of nomos and phusis. This thesis has been in fifth century B.C as the contradiction of phusis and nomos among big thinkers. In this essay, we tried to investigate the relation of phusis and nomos in Plato’s thoughts according to current theories of the contradiction of these in dialogues Gorgias, Republic and Protagoras. Plato tries to minimize consequences of belief to contradiction of phusis and nomos in social and political life by assertion large scale relation between phusis and nomos. Plato depicts the ultimate solution of this problem in Law. There he accounts nomos as raised from phusis that is sub sovereignty of divine. Indeed union of phusis and gods in Plato’s thought is sanction for the identity of phusis and nomos.